"The fall" by Albert Camus and rise of Jacek Dobrowolski - Polak, Marcin (Hybris, 2016)
The Rise and the Fall of the Modern Man is an excellent philosophical essay written by Jacek Dobrowolski. The author – which is contemporary, existential nihilist with pretensions to a minimum of compassion-morality – tracks the development of the idea of the modern subjectivity, swinging between literature and philosophy. He mastered the rare art of concise updates of momentous philosophical issues, by which he refers in hedge-hopping vivacious style. The review notes the advantages (and shortcomings) of the essay, exposing the main focal points present in its insightful narration developed from disenchanted antiquity to the exhausted post-modernity.